A pre-test and post-test study of the physical and psychological effects of out-of-home respite care on caregivers of children with life-threatening conditions. (March 2015) - Remedios, Cheryl; Willenberg, Lisa; Zordan, Rachel; Murphy, Andrea; Hessel, Gail; Philip, Jennifer
Background: Respite services are recommended as an important support for caregivers of children with life-threatening conditions. However, the benefits of respite have not been convincingly demonstrated through quantitative research. Aim: To determine the impact of out-of home respite care on levels of fatigue, psychological adjustment, quality of life and relationship satisfaction among caregivers of children with life-threatening conditions. Design: A mixed-methods, pre-test and post-test study Setting/participants: A consecutive sample of 58 parental caregivers whose children were admitted to a children's hospice for out-of-home respite over an average of 4 days. Results: Caregivers had below-standard levels of quality of life compared to normative populations. Paired t -tests demonstrated that caregivers' average psychological adjustment scores significantly improved from pre-respite (mean = 13.9, standard error  =  0.71) to post-respite (mean = 10.7, standard error = 1); p  < 0.001, 95% confidence interval: 1.25–5.11). Furthermore, caregivers' average fatigue scores significantly improved from pre-respite (mean = 14.3, standard error = 0.85) to post-respite (mean = 10.9, standard error = 1.01; p  < 0.001, 95% confidence interval: 1.69–7.94), and caregivers' average mental health quality of life scores significantly improved from pre-respite (mean = 44.2, standard error = 1.8) to post-respite (mean = 49.1, standard error = 1.6; p  < 0.01, 95% confidence interval: −9.56 to 0.36). Qualitative data showed caregivers sought respite for relief from intensive care provision and believed this was essential to their well-being. Conclusion: Findings indicate the effectiveness of out-of-home respite care in improving the fatigue and psychological adjustment of caregivers of children with life-threatening conditions. Study outcomes inform service provision and future research efforts in paediatric palliative care.